Faith development of high school students: Literature study - Sari, Yunita; Fitri, Susi; Badrujaman, Aip (Universitas Islam Negeri Raden Intan Lampung, 2021)
Spirituality and religiosity can be assets for adolescent development. The purpose of this study is to describe the development of faith that occurs in adolescents. This research is a literature study, where the data required in this study were obtained through analysis of various literature. The results of the study can be explained that adolescents who are at the high school education level and aged 14-18 years are at level 3, namely synthetic-conventional faith. In this case, adolescents begin to develop formal operational thinking and begin to integrate learned faith values into a more rational faith system. For adolescents, this is an intellectual challenge to be able to become a foundation for understanding faith that will continue to develop in developing an understanding of faith in the future. This result implies the importance of guidance and counselling teachers to develop guidance and counselling programs that aim to help students achieve age-appropriate religious development.